Effect of polyethylene glycol on BaTiO3 nanoparticles prepared by hydrothermal preparation. Issue 3 (18th June 2020) - Peng, Yanfen; Chen, Huiling; Shi, Feng; Wang, Jing
Abstract : This work investigated the effect of polyethylene glycol (PEG) as an additive on barium titanate (BaTiO3, BT) nanoparticles (NPs) synthesised by a hydrothermal process. The structure, morphology, dispersion and crystallinity of BT NPs were tested by differential scanning calorimetry–thermogravimetric analysis, X‐ray diffraction, field emission scanning electron microscope, transmission electron microscope and Raman spectroscopy, respectively. The results showed that the main phase of BT NPs includes the cubic BT phase with a tiny tetragonal phase. Also, the addition of PEG with different concentrations has a very positive effect on the control of the grain size and grain shape of the samples during the hydrothermal process. When the concentration of PEG is 1 g/l, BT NPs possess the best morphologies and highest dispersibility, and the average size is about 71.86 nm.